Electrothermal Silver Nanowire Thin Films for In-Situ Observation of Thermally-Driven Chemical Processes - Martínez, E.D. (2018)
Fil: Pastoriza, H. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina